Longitudinal Analysis of Tetanus- and Influenza-Specific IgG Antibodies in Myeloma Patients. (12th March 2012) - Kobold, Sebastian; Luetkens, Tim; Bartels, Britta Marlen; Cao, Yanran; Hildebrandt, York; Sezer, Orhan; Reinhard, Henrike; Templin, Julia; Bartels, Katrin; Lajmi, Nesrine; Haag, Friedrich; Bokemeyer, Carsten; et al.
Abstract : Background . Multiple myeloma (MM) and its therapies may induce a severely compromised humoral immunity. We have performed a longitudinal analysis of IgG-antibody responses against influenza virus (FLU) and tetanus toxoid (TT) as surrogate markers for the B cell-mediated immunity in MM patients. Methods . 1094 serum samples of 190 MM patients and samples from 100 healthy donors were analyzed by ELISA for FLU- and TT-specific antibodies. Results . MM patients evidenced lower levels of FLU- and TT-specific antibodies than healthy controls (P < 0.001 ). Immunoreactivity decreased with progressing disease and worsening clinical status. Levels of FLU- and TT-specific antibodies increased shortly (0-6 months) after alloSCT (P < 0.001 ), a time-period during which intravenous immunoglobulin (IVIG) is routinely applied. Thereafter, antibody concentrations declined and remained suppressed for 3 years in the case of FLU-specific and for more than 5 years in the case of TT-specific antibodies. Conclusions . We found that MM is associated with a profound disease- and therapy-related immunosuppression, which is compensated for a few months after alloSCT, most likely by application of IVIG. This and the differences regarding the recovery of anti-FLU and anti-TT antibody titers during the following years need to be taken into account for optimizing IVIG application and immunization after alloSCT.